Preference Erosion and Multilateral Trade Liberalization - François, Joseph; Hoekman, Bernard; Manchin, Miriam (World Bank, Washington, DC, 2012)
Because of concern that OECD tariff reductions will translate into worsening export performance for the least developed countries, trade preferences have proven a stumbling block to developing country support for multilateral liberalization. The authors examine the actual scope for preference erosion, including an econometric assessment of the actual utilization and the scope for erosion estimated by modeling full elimination of OECD tariffs, and hence full most-favored-nation liberalization-based preference erosion. Preferences are underutilized due to administrative burden-estimated to be at least 4 percent on average-reducing the magnitude of erosion costs significantly. For those products where preferences are used (are of value), the primary negative impact follows from erosion of EU preferences. This suggests the erosion problem is primarily bilateral rather than a WTO-based concern.